ANALISIS PERBANDINGAN REGULASI DI SEKTOR PERTANIAN SEBELUM DAN SESUDAH IMPLEMENTASI PSAK 69 TENTANG PERTANIAN - Samuel Simanjuntak; Lindrianasari Lindrianasari; Ninuk D. Kesumaningrum; Reni Oktavia (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
Implementation of PSAK 69 Agriculture was second year implemented, since 1 January 2018. Mostly, every new regulation have a pro and contra for assumed this regulation. PSAK 69 is the hope of agriculture business actors regarding the clarity of regulations that accommodate agricultural business activities. Because before PSAK 69 was inforced, there is no regulation can accommodate the agriculture business on specific. So, this study wants to explain how implementation PSAK 69 for annual report in many agriculture companies, and give an explaination what’s the difference of the regulation before implementation PSAK 69 and after implementation PSAK 69.